PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DAN XI IPS DI SMA MUHAMMADIYAH BANGKINANG - Isma wardina; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aims of this research was to determine the effect of learning habits and family environment on student achievement on economic subjects class X and XI IPS at SMA Muhammadiyah bangkinang. The Population of this research were students of X dan XI social class at SMA Muhammadiyah bangkinang and the total is 44 students. This Research takes all of population as a sample or is called a cencus study. The data collection was done by using documentation and questionnaire. And the data analysis by using multiple regression analysis. The results of this research indicate (1) study habits have a significant effect on learning achievement with tcount (3,910) > ttabel (2,020) or sig. (0,011) < 0,05 (2) family environment have significant effect to learning achievement with value fcount (32,262) > ftabel (3,226) with sig. (0,000) < 0,05 with a R square value 0,661. It could be concluded that the perchantage of influence of learning habit and family environment to learning achievement variable was equal 61,6%. While the remaining 38,9% influenced by other variables were school environment, community environment, self motivation. Multiple regression equation obtained in this research was = 40,112 + 0,398 + 0,437. It means that if the study habits (X1) and family environment (X2) does not exist then the amount of learning achievement (Y) equal 40,112 and every existence of increase of habit learning then will improve the student achievement of 0,398 and any increase in attention from the family environment will increase student achievement of 0,437.Keywords: Study Habits, Family Environment And Learning Achievement